PROFIL SOSIAL EKONOMI PENDUDUK BALI (TINJAUAN DESKRIPTIF SELAMA KRISIS) - Dayuh Rimbawan, Nyoman (PIRAMIDA; Vol. 1, No. 1 April 2005)
Until now, economy of Bali has not been fully recovered from the impact of economic crisis. The recovery is more restricted by the Kuta bomb blast in the year of 2000 which is followed by decreasing of foreign tourist visit drastically. The economic crisis and the Kuta bomb blast caused several aspect of life of the community become worse, such as decreasing of per capita income, decreasing of life expectancy, and the education qualification in general is not getting better. The decreasing of social and economic life standard of the community is shown by the decreasing of Human Development Index, from 70 in 1996 become 68 in 2002.
Keywords: economic crisis, per capita income, economic life standard